The Effect Of Greenhouse Gas Emissions Disclosure And Environmental Performance On Firm Value: Indonesia Evidence - Gabrielle, Gabrielle; Toly, Agus Arianto (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 14 No 1 (2019), 2019)
This study aimed to investigates the effect of greenhouse gas emissions disclosure and environmental performance on firm value. The samples were companies participating in the Performance Rating Assessment Programme on Environment Management (PROPER/Program Penilaian Peringkat Kinerja Perusahaan) of the Ministry of Environment Republic of Indonesia that are listed in the Indonesia Stock Exchange (BEI) 2014-2017 period. The data used were secondary data from annual reports and/or sustainability reports. This study uses moderated regression analysis with panel data processed by using EViews. The results of this research found that greenhouse gas emissions disclosure and environmental performance have a positive effect on firm value. Environmental performance can moderate the relationship between greenhouse gas emissions disclosure and firm value. Debt to equity ratio and net operating income as control variables have a positive effect on firm value, but firm size has a negative effect on firm value. Keywords: Carbon Disclosure; Greenhouse Gas Emissions; Environmental Performance; Firm Value